A more efficient process to develop protein films derived from agro-industrial by-products. (January 2019) - Garrido, Tania; Peñalba, Miriam; de la Caba, Koro; Guerrero, Pedro
Abstract: Soy protein isolate (SPI) and hydrolyzed keratin (HK) were employed to develop compression molded films. In contrast to other studies, in which toxic chemicals or expensive methods are usually employed to hydrolyze feather keratin, in this research a novel approach was addressed. A solution of NaOH (1 M) was employed and the use of high temperatures was avoided during the process in order to obtain a simple, environmentally friendly and inexpensive method to hydrolyze feather keratin, which can be used for the development of thermoplastic films. In addition to the valorization of agro-industrial waste, the main aim of the incorporation of hydrolyzed feather keratin into film forming formulations was to increase the sulfur content and, thus, the ability to form disulphide bonds, improving the chemical and thermal stability of the resulting films. Graphical abstract: Highlights: Chicken feathers were used to extract keratin by a more sustainable method. Incorporation of hydrolyzed keratin promoted the increase of disulphide bonds. Addition of hydrolyzed keratin provided thermal and mechanical stability to films.